Analisis cemaran bakteri Staphylococcus aureus pada daging ayam krispy pinggir jalan dan fast food di daerah Teladan kota Medan - Adelia Ramadani; Yayuk Putri Rahayu; M. Pandapotan Nasution; Rafita Yuniarti (Journal of Pharmaceutical and Sciences, 2023)
Chicken meat is a highly nutritious food containing protein, fat, minerals and other substances. Chicken meat is easily contaminated with the pathogen Staphylococcus aureus which can cause Staph Food Poisoning (SFP) or food poisoning due to contamination from unhygienic traders, processing, and the environment. The purpose of this study was to identify the presence of S. aureus pathogenic bacteria in roadside crispy fried chicken meat and well-known fast food brands in the Teladan area of Medan city and to analyze the contamination value of S. aureus bacteria whether it meets the Indonesian National Standard (SNI) < 1X102 CFU/ml. The research method was to determine the presence of S. aureus in the sample using Baird Parker Agar Base (BPA) and Egg Yolk media. Specific identification using Gram stain test, coagulase test, and catalase test. Calculation of contamination value of S. aureus with Total Plate Count (TPC). The results on roadside crispy fried chicken were positive for the presence of S. aureus with a contamination value exceeding the threshold above 1X102 CFU/ml so it did not meet SNI standards. Fast food crispy fried chicken meat is known to be negative in the absence of S. aureus pathogenic bacteria so that it meets SNI standards.